Gambaran Penggunaan Insektisida Rumah Tangga di Kelurahan Tangkerang Barat Kecamatan Marpoyan Damai, Pekanbaru - Elva Susanty; Yolazenia Yolazenia; Dedi Afandi; Suri Dwi Lesmana; Mislindawati Mislindawati; M.Farhan Akhyar; M.Randy Kurniadi; M.Teguh Hutomo (Fakultas Kedokteran Universitas Riau, 2023)
Dengue Hemorrhagic Fever (DHF) is a potentially fatal disease that threatening global health, including Indonesia. Various efforts have been made to control DHF, one of them is by means of vector control. Household based insecticides are widely used by the community in controlling insect vectors, including Ae.aegypti as the main vector of DHF. This study aimed to describe the use of household insecticides in the Tangkerang Barat Sub District, Marpoyan Damai District. This study was conducted in September-November 2022 with a total of 100 respondents. The sample selection technique used was simple random sampling from 4 RWs. Data collection was carried out using guided interviews with 4 questions to respondents who used insecticides. Data analysis was carried out using univariate analysis. This study showed that almost all respondents (98%) used household insecticides, the most widely used type of formulation was aerosol (51%), active ingredient was dimeflutrin 0.02%; cypermethrin 0.10% (25.5%), used once a day (75.5%) and used at night (98%). Improper use of household insecticides can have negative effects on the environment, humans, and the occurrence of resistance. Mosquito Nest Eradication needs to be further improved in controlling Ae.aegypti.